Can a pure real business cycle model explain the real exchange rate: The case of Ukraine - Kateryna Onishchenko (Cardiff University, Cardiff Business School, 2011)
Real exchange rate (RER) is an important instrument for restoring sustainable economic growth in the small open economy with large export share. RER of Ukrainian currency can be explained within the real business cycle (RBC) framework without any forms of nominal rigidities. Fitting Ukrainian quarterly data for the period of 1996:Q1-2009:Q3 into the small open economy real business cycle model and testing it by method of indirect inference shows that RER can be reproduced by RBC framework. The generated pseudo-samples for RER by method of bootstrapping allow to obtain the distribution of the best fit ARIMA(2,1,4) parameters and to show with the Wald statistics that those parameters lie within 95% confidence intervals of those estimated for bootstrapped pseudo Q parameters.
Keywords: E31; E32; E37; F31; F37; 330; sustainable economic growth; business cycle; real exchange rates; small open economy; indirect inference; ARIMA; Real Business Cycle; Kaufkraftparität; Nachhaltige Entwicklung; Kleines-offenes-Land; Ukraine